KONTRIBUSI PROGRAM PLP 2 TERHADAP PEMBENTUKAN IDENTITAS PROFESIONAL GURU PADA MAHASISWA - Ilham; Imran Gusnaldi; Muhammad Yusril; Julianti Triyani Syaputri M; Andi Ishlah Hanief Padmanegara; Sarmila; Nabila Annisa; Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The School Field Recognition Program 2 (PLP 2) constitutes a critical stage in the professional identity formation of pre-service teachers. This study aims to describe the process of teacher professional identity formation, identify contributing factors, analyze challenges encountered, and illustrate the shifts in students' self-perceptions before and after PLP 2 implementation. A qualitative case study approach was employed, involving 16 informants comprising 11 students from three study programs at FKIP Universitas Muhammadiyah Bone, 3 cooperating teachers, and 2 field supervisors at SMAN 4 Bone. The 45-day practicum (January 22–March 7, 2026) provided rich empirical ground for analysis. Data were collected through in-depth interviews, participatory observation, focus group discussions, daily reflective journals, and documentation. Data analysis followed the Miles, Huberman, and Saldaña model. Findings reveal that PLP 2 significantly contributes to teacher professional identity formation across five core themes: awareness of the teacher role, development of teaching self-efficacy, internalization of professional values, identity adaptation within school communities, and transformative reflection on the teaching profession. The most influential factors were cooperating teacher mentorship and authentic classroom teaching experience. The novelty of this study lies in the construction of a layered teacher professional identity formation model specific to the PLP 2 context in Indonesia.